2016
DOI: 10.1371/journal.pone.0149855
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Renal Sympathetic Denervation on Left Ventricular Structure and Function at 1-Year Follow-Up

Abstract: BackgroundCatheter-based sympathetic renal denervation (RDN) is a recent therapeutic option for patients with resistant hypertension. However, the impact of RDN in left ventricular (LV) mass and function is not completely established. Our aim was to evaluate the effects of RDN on LV structure and function (systolic and diastolic) in patients with resistant hypertension (HTN).Methods and ResultsFrom a single centre prospective registry including 65 consecutive patients with resistant HTN submitted to RDN betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 31 publications
0
7
1
2
Order By: Relevance
“…With regards to cardiac function, both E/e’ and EF were improved at 6 months, but none of them changed at 12 months. One potential explanation is that the number of trials included at 12 months was too small (only 2) 21 , 24 , and therefore it may be difficult to derive a conclusive analysis. More future studies should consider a longer follow up duration.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to cardiac function, both E/e’ and EF were improved at 6 months, but none of them changed at 12 months. One potential explanation is that the number of trials included at 12 months was too small (only 2) 21 , 24 , and therefore it may be difficult to derive a conclusive analysis. More future studies should consider a longer follow up duration.…”
Section: Discussionmentioning
confidence: 99%
“…[37] The difference in BP reduction between the 2 groups was À13 mmHg in favor of the RDN group. Left ventricular hypertrophy and left atrial enlargement are themselves risk factors for the development of atrial fibrillation, but RDN has been reported to improve them [19,[51][52][53][54] and a randomized sham-controlled trial using cardiac MRI showed that the stroke volume index was reduced by 4.7 mL/m 2 in the RDN group (difference between the 2 groups P = 0.008). [55] Furthermore, RDN has significantly improved the 6-minute walk in patients with chronic heart failure.…”
Section: Safety Of the Rdn Proceduresmentioning
confidence: 99%
“…Коронарный резерв в трансмуральных сосудах, кровоснабжающих субэндокардиальные отделы сердца, даже в норме выраженно снижается по сравнению с субэпикардиальными артериями. Это снижение становится особенно значительным при повышении диастолического дав- [53][54][55][56][57][58][59] ления в ЛЖ у больных АГ и возрастании экстравазальной компрессии вследствие возникновения ГЛЖ [21,22]. Следует учитывать, что изменения трансмурального коронарного кровотока и коронарной микроциркуляции в ответ на действие психоэмоциональных и физических факторов модулируют преимущественно коронарные преартериолы и артериолы диаметром < 500 μm.…”
Section: Conflict Of Interestunclassified
“…и 74,0 ± 9,0 мм рт. ст., p < 0,001) приводило к значительному уменьшению индекса ММ ЛЖ (152,0 ± 32,0 и 136,0 ± 34,0 г/м 2 ; p < 0,001) [59]. Отчетливый регресс ГЛЖ, по данным МРТ в отечественном исследовании по изучению кардиопротективных эффектов ренальной денервации, выполненном при включении 84 больных, не только не зависел от выраженности антигипертензивного эффекта лечения, но выявлялся и у пациентов с отсутствием должного снижения АД.…”
Section: Conflict Of Interestunclassified